Lima Bean - Peraza Mercado, Gwendolyne (Springer, 2020)
According to the taxonomy, the bean belongs to the genus Phaseolus, which includes approximately 35 species of which 4 are cultivated: P. vulgaris L.; P. lunatus L.; P. coccineus L., and P. acutifolius L. (Arias-Restrepo et al. 2007). Phaseolus lunatus L. belongs to the Fabaceae family, and there are two domesticated genetic stocks from two different wild forms with two seed morphologies, small and large (Debouk 2019). The small seeds are known as ib., patashete and futuna (Yucatan, Chiapas, and Jalapa, Mexico, respectively), caballero bean (Cuba), ixtapacal (Guatemala), chilipuca (El Salvador), haba (Puerto Rico and Panama), sieva and comba (Colombia), and guaracaro (Venezuela), among others. The large seeds are known as lima, layo and pallar (Peru), torta (Colombia), palato (Bolivia), and manteotto (Argentina) (Debouk 2019). It is proposed that P. lunatus could have originated in the Neotropical region of America, ranging from Mexico to Chile, passing through the Andean region of Peru. It is believed that its origin is found in Guatemala since in this area the wild progenitor of this species was found; on the other hand, molecular studies propose that its origin is found in the Andean zone and that its distribution throughout the Americas was given by domestication (FAO 2018).